Toll-like receptors 7 and 9 regulate the proliferation and differentiation of B cells in systemic lupus erythematosus - Wen, Luyao; Zhang, Bei; Wu, Xinfeng; Liu, Rongzeng; Fan, Hua; Han, Lei; Zhang, Zhibo; Ma, Xin; Chu, Cong-Qiu; Shi, Xiaofei (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE) is an autoimmune illness marked by the loss of immune tolerance and the production of autoantibodies against nucleic acids and other nuclear antigens (Ags). B lymphocytes are important in the immunopathogenesis of SLE. Multiple receptors control abnormal B-cell activation in SLE patients, including intrinsic Toll-like receptors (TLRs), B-cell receptors (BCRs), and cytokine receptors. The role of TLRs, notably TLR7 and TLR9, in the pathophysiology of SLE has been extensively explored in recent years. When endogenous or exogenous nucleic acid ligands are recognized by BCRs and internalized into B cells, they bind TLR7 or TLR9 to activate related signalling pathways and thus govern the proliferation and differentiation of B cells. Surprisingly, TLR7 and TLR9 appear to play opposing roles in SLE B cells, and the interaction between them is still poorly understood. In addition, other cells can enhance TLR signalling in B cells of SLE patients by releasing cytokines that accelerate the differentiation of B cells into plasma cells. Therefore, the delineation of how TLR7 and TLR9 regulate the abnormal activation of B cells in SLE may aid the understanding of the mechanisms of SLE and provide directions for TLR-targeted therapies for SLE.